2015
DOI: 10.1371/journal.pone.0124687
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Dynamics at Early Stages of Molecular Interactions of MYMIV with Resistant and Susceptible Genotypes of the Leguminous Host, Vigna mungo

Abstract: Initial phases of the MYMIV- Vigna mungo interaction is crucial in determining the infection phenotype upon challenging with the virus. During incompatible interaction, the plant deploys multiple stratagems that include extensive transcriptional alterations defying the virulence factors of the pathogen. Such molecular events are not frequently addressed by genomic tools. In order to obtain a critical insight to unravel how V. mungo respond to Mungbean yellow mosaic India virus (MYMIV), we have employed the PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 57 publications
(79 reference statements)
2
29
0
Order By: Relevance
“…The results suggest that this gene may be involved in regulating the expression of some resistance genes or defense mechanisms only in resistant genotype. Kundu et al (2015) evidenced that the expression profiling of transcription factor of this same family (bHLH) may play a complementary and/or overlapping role in enhancing expression of downstream components of the defense pathway.…”
Section: Profiling Of Differentially Expressed Genes (Degs)mentioning
confidence: 99%
“…The results suggest that this gene may be involved in regulating the expression of some resistance genes or defense mechanisms only in resistant genotype. Kundu et al (2015) evidenced that the expression profiling of transcription factor of this same family (bHLH) may play a complementary and/or overlapping role in enhancing expression of downstream components of the defense pathway.…”
Section: Profiling Of Differentially Expressed Genes (Degs)mentioning
confidence: 99%
“…They also observed major changes in the gene expression in resistant genotypes upon MYMIV infection in the jasmonic acid biosynthesis and signal transduction pathways, cell wall modifications, and metabolic pathways (Table 5). Likewise, Kundu et al [167] found 345 candidate genes that illustrate differential expression during compatible or incompatible interactions. They categorized ESTs into nine different functional categories based on their putative functions.…”
Section: Transcriptomics Approachesmentioning
confidence: 99%
“…Since ESTs do not provide any quantitative estimation of gene expression, gene expression of selected ESTs through quantitative PCR will give more accurate information. Kundu et al [167] studied 19 genes related to R-protein such as, the suppressor of the G2 allele of skp1 (SGT1) and heat shock protein 90 (HSP 90), systemic acquired resistance (SAR) indicator gene, pathogenesis-related (PR) genes, genes related to reactive oxygen species (ROS) homeostasis (superoxide dismutase (SOD), ascorbate peroxidase (APOX), thioredoxin (TRX), and metallothionein (MET)), signal transduction gene (such as calmodulin (CAM), and other genes like WRKY, glutathione S transferase (GST), phenylalanine ammonia lyase (PAL), ubiquitin ligase, tryptophan synthase (TS), cysteine protease (CSP), rubisco activase (RuAc), MADS box protein (MADS), auxin response factor (ARF), and oxygen-evolving complex (OEC)), at different time point intervals in both the resistant and susceptible cultivar of V. mungo against MYMIV. They also observed the coordinate action of salicylic acid-responsive pathways, Ca 2+ signaling, redox imbalance, and PR genes.…”
Section: Transcriptomics Approachesmentioning
confidence: 99%
“…In a previous study we have shown that in MYMIV-resistant genotype of blackgram HSP 90 was over-expressed at early hours of viral infection than in Cv. T9 [8]. This further indicates the possibility of functional inability of cyr1 in recognizing MYMIV-CP, perhaps due to folding impairment.…”
Section: Resultsmentioning
confidence: 86%
“…Likewise another set of experimental plants were forcefully fed by the starved, non-viruliferous whiteflies and referred to as mock inoculated control. Accumulation of MYMIV particles in the host plants after challenging with the virus was determined by qPCR as previously reported by Kundu et al [8].…”
Section: Artificial Forced Inoculation Of V Mungo With Mymivmentioning
confidence: 99%